[en] ESTUDO AERODINÂMICO - LUIS DANIEL PERALTA MALDONADO (2021)
[pt] In order to gain deeper understanding of the ow physics around low aspect ratio wings, the current dissertation presents a numerical study of the ow around a race-car rear wing, in particular, the PUC-Rio Formula-University car. To diminish the time it takes to prepare a numerical simulation, we evaluate the performance and accuracy of a particular utility available in Open-FOAM, namely, snappyHexMesh, which generates hexahedral unstructured grids. The effect of using such a grid in numerical simulations employing two different turbulence models (Spalart Allmaras and k - w SST) for several angles of attack is investigated. The methodology of the study comprised six steps: 3D scanning of the real geometry, geometry modeling, grid generation, ow computation, solution validation, ow visualization and analysis. The grid qualities were assessed using a simple two-dimensional case, which showed good agreement with experimental data with an absolute difference ranging between 0.39 per cent and 8 per cent. While comparing them with numerical validated data the difference ranged between 0.5 per cent and 3.6 per cent. By visualizing the velocity and pressure fields, it was confirmed that the methodology used in the current study is capable of capture the various physical phenomena present in the ow around a rear wing, which is characterized by horseshoe vortices at the end plates, local recirculation zones, tip vortices and their interaction with the boundary layer at the suction surface. The simulations showed that the size of the tip and horseshoe vortices increases with the angle of attack, as well as their in uence on the boundary-layer separation. Consequently, although the end plates are known to be useful in reduction of vortex, it was observed there is still a great waste of energy in their formation.